Low frequency of HNPCC-associated microsatellite instability and aberrant MMR protein expression in early-onset bladder cancer - Giedl, Josef; Schneckenpointner, Roland; Filbeck, Thomas; Ruemmele, Petra; Hofstaedter, Ferdinand; Burger, Maximilian; Hartmann, Arndt; Stoehr, Robert (American Journal of Clinical Pathology, 2014)
Recently, it was shown that patients with Lynch syndrome due to an MSH2 mutation are at increased risk for the development of bladder cancer. To further this discussion, we screened the largest investigated cohort of patients with early-onset bladder cancer for microsatellite instability (MSI) and mismatch repair (MMR) deficiency to determine a possible role of Lynch syndrome in young patients with bladder cancer.A total of 109 cases of bladder tumors from young patients (aged <45 years) were examined for MSI (Bethesda consensus panel). Expression of MMR proteins (hMLH1, hMSH2, and hMSH6) was evaluated by immunohistochemistry using a tissue microarray. Results were compared with a series of unselected consecutive bladder tumors (n = 95).Regarding the frequency of MSI high (1% vs 0%) or abnormal expression of MMR proteins (2% vs 6.5%), no significant difference between the early-onset and unselected patient group was found.In young patients with bladder tumors, MSI and defects in MMR protein expression were not more frequent than in a series of consecutive bladder tumors. Most bladder tumors in young patients are not to be attributed to Lynch syndrome.
EVALuna2:6663